1989
DOI: 10.1021/bi00439a042
|View full text |Cite
|
Sign up to set email alerts
|

Activation energy of the slowest step in the glucose carrier cycle: break at 23.degree.C and correlation with membrane lipid fluidity

Abstract: Glucose transport in the rat erythrocyte is subject to feedback regulation by sugar metabolism at high but not at low temperatures [Abumrad et al. (1988) Biochim. Biophys. Acta 938, 222-230]. This indicates that temperature, which is known to alter membrane fluidity, also alters sensitivity of transport to regulation. In the present work, we have investigated a possible correlation between the effects of temperature on rate-limiting steps of glucose transport and on membrane fluidity. The dependences of methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Second, in direct support of our postulate, moderate increases in plasma membrane fluidity have been documented to increase glucose transport [21][22][23]. Studies show that basal glucose transport is not fully active in fat cells and that it can be increased further by augmenting membrane fluidity [21].…”
Section: Introductionsupporting
confidence: 54%
“…Second, in direct support of our postulate, moderate increases in plasma membrane fluidity have been documented to increase glucose transport [21][22][23]. Studies show that basal glucose transport is not fully active in fat cells and that it can be increased further by augmenting membrane fluidity [21].…”
Section: Introductionsupporting
confidence: 54%
“…Although intermittent study has coupled membrane fluidity to insulin sensitivity (48)(49)(50), a mechanistic understanding has remained elusive. It is an interesting thought that PM cholesterol trimming may be a common and key antidiabetogenic action of CrPic and metformin, as well as several other antidiabetic agents known to display AMPK-stimulating and cholesterol-lowering properties, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Because cholesterol causes a highly ordered, gel-like state (9), it is not surprising that a cell's responsiveness to insulin may depend on the cell surface membrane fluidity. In agreement with this postulate, studies have documented that moderate increases in plasma membrane fluidity increase glucose transport (13,36,54). Furthermore, it has been shown that basal glucose transport is not fully active in fat cells and can be increased further by augmenting fluidity (13).…”
Section: Discussionmentioning
confidence: 57%